Pengembangan Sistem Informasi Manajemen Keuangan Lesehan & Kolam Pancing Kresna Berbasis Website Menggunakan Model Evolutionary Prototyping - Muhammad Baghiz Firdausa; Retno Indah Rokhmawati; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Lesehan & Kolam Pancing Kresna is a restaurant located in Pacet, Mojokerto which is experiencing problems during the financial management process. The problem is that the financial recording process is still done manually, which causes a mismatch between the recorded money data and the money data held by the restaurant. Another problem is in the reporting process, where the activity from the reporting process is too long to require more effort in making financial reports. The formulation of the problem from this research is how to build an information system that makes it easier to record and prepare financial reports. The purpose of this study is to simplify the process of financial recording and financial reporting. The solution obtained is the creation of a financial management information system which was developed using the evolutionary prototyping method. The conclusion obtained to solve this problem is to simplify the current business process activities (as-is) into a recommendation business process (to-be) by using information systems to facilitate activities. The information system is tested using two types of tests, namely validation testing and user acceptance testing (UAT). Validation testing is carried out to determine whether the system already has a feature under the request and can run smoothly, while user acceptance testing is to measure the level of user acceptance of the information system. The results obtained in the user acceptance testing test are 87% which indicates that the user strongly agrees with the information system that has been developed